2020
DOI: 10.1002/sta4.318
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐Weibull distributions: Generalizing sub‐Gaussian and sub‐Exponential properties to heavier tailed distributions

Abstract: We propose the notion of sub‐Weibull distributions, which are characterized by tails lighter than (or equally light as) the right tail of a Weibull distribution. This novel class generalizes the sub‐Gaussian and sub‐Exponential families to potentially heavier tailed distributions. Sub‐Weibull distributions are parameterized by a positive tail index θ and reduce to sub‐Gaussian distributions for and to sub‐Exponential distributions for . A characterization of the sub‐Weibull property based on moments and on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 12 publications
3
58
0
Order By: Relevance
“…In the literature [31,33], a random variable is often called sub-Gaussian, sub-exponential, or sub-Weibull with tail parameter (1/α), if X ψ2 ≤ C, X ψ1 ≤ C, and X ψα ≤ C, respectively. The matrix spectral norm is defined as X = sup u,v u Xv u 2 v 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the literature [31,33], a random variable is often called sub-Gaussian, sub-exponential, or sub-Weibull with tail parameter (1/α), if X ψ2 ≤ C, X ψ1 ≤ C, and X ψα ≤ C, respectively. The matrix spectral norm is defined as X = sup u,v u Xv u 2 v 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Let g(x)=e x θ −1 and E[g(|X|/η)]≤1 implies E[exp(|X| θ /η θ )]≤2, which is the definition of sub-Weibull norm. Similar to sub-exponential,[85,89,96] attained the following.…”
mentioning
confidence: 77%
“…The proof can be found in [85,89] by mimicking the proof of [84, Proposition 2.5.2]. It follows from Corollary 6.1(4) that X is sub-Weibull with tail parameter θ if and only if |X| 1/θ is sub-exponential.…”
Section: Corollary 61 (Characterizations Of Sub-weibull Condition)mentioning
confidence: 92%
“…In our analysis, we associate the gradient error with a class of potentially heavy tailed probability distributions. As in [52], we consider class of sub-Weibull random variables as defined next.…”
Section: Stochastic Projected Primal-dual Methodsmentioning
confidence: 99%
“…Empirical and theoretical results have demonstrated that heavier tailed distributions arise naturally in deep learning. The class of sub-Weibull random variables subsumes the sub-Guassian and sub-Exponential classes of distributions, while also including heavier tailed distributions [30,52,55]. It also includes random variables whose distribution has a bounded support.…”
Section: Related Workmentioning
confidence: 99%